2016
DOI: 10.1186/s12879-016-2034-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of melioidosis in Cambodian children, 2009–2013

Abstract: BackgroundMelioidiosis, infection by Burkholderia pseudomallei, is an important but frequently under-recognised cause of morbidity and mortality in Southeast Asia and elsewhere in the tropics. Data on the epidemiology of paediatric melioidosis in Cambodia are extremely limited.MethodsCulture-positive melioidosis cases presenting to Angkor Hospital for Children, a non-governmental paediatric hospital located in Siem Reap, Northern Cambodia, between 1st January 2009 and 31st December 2013 were identified by sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 21 publications
2
47
1
4
Order By: Relevance
“…A large study in Cambodia has also recently reported extremely high pediatric melioidosis incidences (28–35 cases per 100,000 children) [26]. In fact, the pediatric incidence rates recorded in this Cambodian study, and in the present one, are comparable to that of adult cases in northern Australia (19.6/ 100,000) and northeast Thailand (21.3/ 100,000) [27, 28], highlighting the significant and likely unrecognized burden of melioidosis in children.…”
Section: Discussionmentioning
confidence: 99%
“…A large study in Cambodia has also recently reported extremely high pediatric melioidosis incidences (28–35 cases per 100,000 children) [26]. In fact, the pediatric incidence rates recorded in this Cambodian study, and in the present one, are comparable to that of adult cases in northern Australia (19.6/ 100,000) and northeast Thailand (21.3/ 100,000) [27, 28], highlighting the significant and likely unrecognized burden of melioidosis in children.…”
Section: Discussionmentioning
confidence: 99%
“…A male‐biased incidence was found among the neonatal melioidosis cases (68%; 15/22), similar to childhood and adult melioidosis . The odds of fatal outcome were found 3.67 times higher among male than the odds were among female neonates.…”
Section: Discussionmentioning
confidence: 81%
“…Neonatal melioidosis is considered a rare infection even in endemic regions . The only children hospital in Sabah, for example, had only two confirmed cases on record in year 2000‐2012 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations